Ordoliberalism, state, and society : a political theory of social order - Malatesta, Olimpia, 1989- (Routledge, 2025)
"This book provides a new interpretation of ordoliberalism - the influential German version of neoliberalism - by exploring the political, legal, and social context of its emergence. Ordoliberal scholars regarded sociology, juridical science, and economics as concrete policy-making instruments designed to discipline the structural conflicts of modern society. For, in their view, society should not impinge on the economy. Ordoliberalism is here presented as a political theory of social order, developing out of the the crisis of the Weimar Republic, and which has proven to be one of the most influential neoliberal accounts of social organization after WWII. Assessing the influence that leading German intellectuals such as Sombart, Schmoller, Savigny and Schmitt have exerted on ordoliberalism, this book provides an in-depth analysis of the social, legal, and political theory of Walter Eucken, Franz Böhm, Alfred Müller-Armack, Wilhelm Röpke and Alexander Rüstow. In so doing, the book offers an invaluable study of the ideological roots of the notion of an economic constitution, and a political-theoretical analysis of one of the first articulations of authoritarian liberalism at the European level. This book will appeal to scholars and students of legal, social, political and economic theory"-- Provided by publisher.
Keywords: Law and economics.; Economic development.; Social justice.; Sociological jurisprudence.; Neoliberalism -- Europe.; Law -- Political aspects -- Europe.; Law -- Economic aspects -- Europe.; Law -- Social aspects -- Europe.; elektronické knihy; electronic books